Das House-Kapital : A Long Term Housing and Macro Model - Grossman, Volker; Steger, Thomas (Washington, D.C. : International Monetary Fund, 2017)
There are, by now, several long term, time series data sets on important housing and macro variables, such as land prices, house prices, and the housing wealth-to-income ratio. However, an appropriate theory that can be employed to think about such data and associated research questions has been lacking. We present a new housing and macro model that is designed specifically to analyze the long term. As an illustrative application, we demonstrate that the calibrated model replicates, with remarkable accuracy, the historical evolution of housing wealth (relative to income) after World War II and suggests a further considerable increase in the future. The model also accounts for the close connection of house prices to land prices in the data. We also compare our framework to the canonical housing and macro model, typically employed to analyze business cycles, and highlight the main differences.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet